Konflik Prioritas Anggaran Pendidikan di Kota Depok: Pengadaan Papan Tulis Interaktif Rp30 Miliar di Tengah Kebutuhan Dasar yang Belum Terpenuhi - Naila Azaria Arumi; Naura Rania Bari; Nova Jojor; Silvia Zahra Zahira; Ridwan Ridwan; Maisarah Mitra Adrian (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Education budgeting has become an increasingly relevant issue as local governments face competing priorities between advancing educational modernization and addressing schools’ fundamental needs. This study aims to examine how the 2025 Depok City Regional Budget allocation of IDR 30 billion for interactive whiteboard procurement reflects priority conflicts in local education budgeting while essential educational facilities remain unevenly fulfilled. This research employed a qualitative approach using a single case study design. Data were collected through document analysis of local government documents, budget records, news reports, and relevant academic literature. Data analysis was conducted using thematic analysis and qualitative content analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that education budget allocation in Depok illustrates tensions between educational digitalization initiatives and the fulfillment of schools’ basic infrastructure needs. The study also found that budget priority setting is shaped by differences in orientation among government actors, limited policy transparency, and public participation that remains less than optimal. Although educational technology has the potential to support learning quality, its effectiveness depends heavily on school infrastructure readiness and the supporting capacity required for implementation.